Mutated VWA8 Is Associated With Developmental Delay, Microcephaly, and Scoliosis and Plays a Novel Role in Early Development and Skeletal Morphogenesis in Zebrafish - Umair, Muhammad; Farooq Khan, Muhammad; Aldrees, Mohammed; Nashabat, Marwan; Alhamoudi, Kheloud M.; Bilal, Muhammad; Alyafee, Yusra; Al Tuwaijri, Abeer; Aldarwish, Manar; Al-Rumayyan, Ahmed; Alkhalaf, Hamad; Wadaan, Mohammad A. M.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Von Willebrand A domain-containing protein 8 (VWA8), also named KIAA0564, is a poorly characterized, mitochondrial matrix-targeted protein having a putative ATPase activity. VWA8 is comprising of ATPase-associated domains and a VWFA domain associated with ATPase activity inside the cell. In the present study, we describe a large consanguineous family of Saudi origin segregating a complex developmental syndrome in an autosomal recessive fashion. All the affected individuals exhibited severe developmental disorders. DNA from three patients was subjected to whole-exome sequencing followed by Sanger sequencing. VWA8 knock-down zebrafish morpholinos were used to study the phenotypic effect of this gene on zebrafish development. A homozygous missense variant [c.947A > G; p.(Asp316Gly)] was identified in exon 8 of the VWA8 gene, which perfectly segregated with the disease phenotype. Using zebrafish morpholino, we observed delayed development at an early stage, lack of movement, light sensitivity, severe skeletal deformity such as scoliosis, and facial dysmorphism. This is the first homozygous variant identified in the VWA8 gene underlying global developmental delay, microcephaly, scoliosis, limbs, and cardiovascular malformations in humans. We provide genetic and molecular evidence using zebrafish morpholino for a homozygous variant in the VWA8 gene, associated with such a complex developmental syndrome in humans.